Leprosy among children under 15 years of age: literature review - Marcela Bahia Barretto de Oliveira; Lucia Martins Diniz (Sociedade Brasileira de Dermatologia, 2016)
Abstract Leprosy is a chronic infectious disease caused by Mycobacterium leprae, representing a public health issue in some countries. Though more prevalent in adults, the detection of new cases in children under 15 years of age reveals an active circulation of bacillus, continued transmission and lack of disease control by the health system, as well as aiding in the monitoring of the endemic. Among patients under 15 years of age, the most affected age group is children between 10 and 14 years of age, although cases of patients of younger than 1 year of age have also been reported. Household contacts are the primary source of infection, given that caretakers, such as babysitters and others, must be considered in this scenario. Paucibacillary forms of the disease prevailed, especially borderline-tuberculoid leprosy, with a single lesion in exposed areas of the body representing the main clinical manifestation. Reactional states: Lepra reactions are rare, although some authors have reported high frequencies of this phenomenon, the most frequent of which is Type 1 Lepra Reaction. Peripheral nerve involvement has been described at alarming rates in some studies, which increases the chance of deformities, a serious problem, especially if one considers the age of these patients. The protective effect of BCG vaccination was found in some studies, but no consensus has been reached among different authors. Children must receive the same multidrug therapy regimen and the doses should, ideally, be calculated based on the child´s weight. Adverse reactions to this therapy are rare within this age group. This article aims to review epidemiological, clinical, and therapeutic aspects of leprosy in patients under 15 years of age.